Social and Solidarity Economy in Bulgaria and Romania: Challenges and Opportunities - Marinova, Tsvetelina (Research Papers, 2022)
In the Balkans, the modern development of the social and solidarity economy has resulted primarily from the economic and social challenges faced by the countries during the transition, the low efficiency of national institutions and social policies and the limited redistributive capacity of the state, as well as their geopolitical and economic orientation to the European Union and the transfer of ideas and institutions from the developed European countries. The study covers two Balkan countries (Bulgaria, Romania). It presents the concepts and policies in the sector and discusses the main challenges it faces, as well as the opportunities for its future development.
Keywords: Bulgaria; Social and solidarity economy; Social enterprises; Romania; Cooperatives; Europe; Public Policy